Understanding the Teacher-students’ Presuppositions in the Classroom Interaction - Dewi, Indah Riskiana; Susanto, Fajar (JET ADI BUANA, 2023)
The aim of this study is to examine the presuppositions that occur between teachers and students during classroom interactions. The study employed a qualitative descriptive approach to describe the teachers and students’ interactions in the classroom and how the presuppositions can be understood well in their interactions. The data were collected through recording method during the classroom interactions. Descriptive analysis was used to categorize and interpret the data, and lead to the identification of five types of presuppositions: existential, factive, lexical, structural, and non-factive presupposition. The study found that each utterance contained various forms that indicated presuppositions, and each type of presuppositions was not exclusively indicated by a specific word-form. Therefore, categorizing each type of presupposition requires consideration of the contexts of the speaker's discussion, rather than solely looking at the phrase used.